4 3 2 1: A Listening - Priyanka Deshmukh (Revue LISA)
Scholarly studies dedicated to Paul Auster’s works over the past decade have tended to focus on his storytelling, addressing, for the most part, thematic and formal concerns. The relatively small amount of scholarship on Auster’s stylistic and linguistic maneuvers is perhaps due to the fact that he uses an apparently prosaic and conventional style: grammatically sound sentences do not draw attention. Yet, in all its plainness, Auster’s language is abundantly musical. In his latest novel, 4 3 2 1, by making the reader count down in order to access the first page of the novel, almost like the opening of a piece of music with a 4/4 time signature, Auster calls attention to the sounds his words make, to their music, and to the orality of his prose. This paper listens closely to the sounds in 4 3 2 1, and reads in it a musicality, a rhythm that structures the sequence of events that order his narration, but also studies the interplay between music, words, sound, silence and language, that makes it stand out among Auster’s other works.